(untitled) (Journal of the Bangladesh Agricultural University, 2025)
The aim of this paper is to provide a comprehensive overview of fry production and induced breeding practices in fish hatcheries located in Mymensingh district of Bangladesh. A pre-planned questionnaire survey was used to gather primary data regarding fry production, breeding methodologies, and operational aspects of hatcheries. The study shows that 40% of the hatchery owners belong to middle age group followed by old (33.33%) and young (26.67%) age group. The lack of formal training for more than half of the respondents could impact the efficiency and sustainability of hatchery operations. Hatcheries in the study area vary in size and physical facilities. Induced breeding practices involving administration of exogenous hormones to stimulate ovulation and spawning, were found to be widely adopted in the surveyed hatcheries. Fry production and price in depended on fish species and production period. In the fish seed marketing channel, the intermediaries were the main stakeholder. Hatchery owner reported the occurrence of diseases including argulosis, fin rot, epizootic ulcerative syndrome (EUS), skin lesion, swollen abdomen, and fungal infection in different seasons. Various types of chemicals and drugs were found to use in the surveyed fish hatchery as antibacterial agent, disinfectant, pesticide, fertilizer, and growth promoter. Despite the progress made in fry production and induced breeding practices, the drainage problem, insufficient credit facility, theft, market competition, and price fluctuations were identified as critical problems in hatchery management. In conclusion, the results indicate that the Mymensingh district is a vital aquaculture hub. Addressing the identified challenges and implementing the recommended strategies such as expanding access to training for hatchery operators and establishment of better financial support systems is crucial for enhancing the operational capacity of hatcheries. J Bangladesh Agril Univ 23(2): 259-268, 2025